Clinical performance of a bone-anchored annular closure device in older adults - Bouma GJ (Dove Medical Press, 2019)
Gerrit J Bouma,1 Ardeshir Ardeshiri,2 Larry E Miller,3 Erik Van de Kelft,4,5 Richard Bostelmann,6 Peter D Klassen,7 Charlotte Flüh,8 Adisa Kuršumović91Department of Neurosurgery, OLVG and Amsterdam University Medical Centers, Amsterdam, the Netherlands; 2Section for Spine Surgery, Klinikum Itzehoe, Itzehoe, Germany; 3Miller Scientific Consulting, Asheville, NC, USA; 4Department of Neurosurgery, AZ Nikolaas, Sint-Niklaas, Belgium; 5Antwerp University, Antwerp, Belgium; 6Department of Neurosurgery, University Clinic Düsseldorf, Duesseldorf, Germany; 7Department of Neurosurgery, St. Bonifatius Hospital, Lingen, Germany; 8Department of Neurosurgery, University Medical Center Schleswig-Holstein, Kiel, Germany; 9Department of Neurosurgery, Donauisar Klinikum Deggendorf, Deggendorf, GermanyBackground: Lumbar discectomy is a common surgical procedure in middle-aged adults. However, outcomes of lumbar discectomy among older adults are unclear.Methods: Lumbar discectomy patients with an annular defect ≥6 mm width were randomized to receive additional implantation with a bone-anchored annular closure device (ACD, n=272) or no additional implantation (controls, n=278). Over 3 years follow-up, main outcomes were symptomatic reherniation, reoperation, and the percentage of patients who achieved the minimum clinically important difference (MCID) without a reoperation for leg pain, Oswestry Disability Index (ODI), SF-36 Physical Component Summary (PCS) score, and SF-36 Mental Component Summary (MCS) score. Results were compared between older (≥60 years) and younger (<60 years) patients. We additionally analyzed data from two postmarket ACD registries to determine consistency of outcomes between the randomized trial and postmarket, real-world results.Results: Among all patients, older patients suffered from crippling or bed-bound preoperative disability more frequently than younger patients (57.9% vs 39.1%, p=0.03). Among controls, female sex, higher preoperative ODI, and current smoking status, but not age, were associated with greater risk of reherniation and reoperation. Compared to controls, the ACD group had lower risk of symptomatic reherniation (HR=0.45, p<0.001) and reoperation (HR=0.54, p=0.008), with risk reductions comparable in older vs younger patients. The percentage of patients achieving the MCID without a reoperation was higher in the ACD group for leg pain (81% vs 72%, p=0.04), ODI (82% vs 73%, p=0.03), PCS (85% vs 75%, p=0.01), and MCS (59% vs 46%, p=0.007), and this benefit was comparable in older versus younger patients. Comparable benefits in older patients were observed in the postmarket ACD registries.Conclusion: Outcomes with lumbar discectomy and additional bone-anchored ACD are superior to lumbar discectomy alone. Older patients derived similar benefits with additional bone-anchored ACD implantation as younger patients.Keywords: annulus fibrosus, disc, elderly, herniation, lumbar, sciatica